(untitled) (Academia Science Repository, 2023)
Social pedagogy, as an interdisciplinary field, combines educational theory, social work principles, and sociocultural perspectives to address the holistic development and well-being of individuals within society. It emphasizes the importance of social interaction, emotional connection, and experiential learning in shaping one’s identity and values. By integrating social pedagogy into educational settings, educators can play a crucial role in nurturing a sense of love for the motherland among students and young learners. social pedagogy plays a vital role in awakening and promoting a sense of love for the motherland among students and young learners. By integrating social pedagogical principles into educational settings, educators can facilitate experiences that foster a deep attachment, appreciation, and commitment to one’s country. By embracing the values of social pedagogy, students can develop a profound sense of love for their motherland, contributing to their personal growth, social cohesion, and active citizenship.